PENGARUH STRATEGI GROUP TO GROUP EXCHANGE TERHADAP HASIL BELAJAR SISWA MATERI VIRUS KELAS X SMA - Kurniati, Kurniati; Ningsih, Kurnia; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The  research work aimed to find out the effect of teaching strategy of group to group exchange on student’s achievement in virus topic in grade X of Senior High School Mujahidin Pontianak. The research was quasi experimental design using nonequivalent control group design. Sample was collected using saturation sampling, grade X MIPA 1 as the experimental group and grade X MIPA 2 as the control group. The instrument consisted of 20 multiple choice questions. The research finding showed that the average score of student’s achievement for the experimental group was 14,94 and  for the control group was 13,24. Based on U Mann Whitney test, the research obtained Zcount (-2,95) < -Ztable (-1,96). This meant that there was a significant differences between student’s achievement using group to group exchange strategy and expository strategy. The effect size score was 0,91 with high category gave big influence by 31,86%. Keywords: Group to group exchange strategy, student’s achievement, virus topic.